Design and Realization of Indicators Management Platform for Large Enterprises - Ying Jiang; Zhiqiang Wang; Hongning Liu; Bo Dai (Dianxin kexue)
The operation indicators of an enterprise reflect its production and operation situation directly，and provide data support for decision aids.The scientific and effective management of operation indicators is the top priority in the data asset management of a large enterprise.Combined with the comprehensive control of data in State Grid Zhejiang Electric Power Company，the model designing ideas of operation indicators and function-realizing way of indicators management platform were summarized，and the realization of scientific and effective management with building up indicators management platform were advanced.